Elevated factor Xa activity in the blood of asymptomatic patients with congenital antithrombin deficiency. - Bauer, K A (1985)
The presence of congenital antithrombin deficiency has been consistently shown to predispose patients to venous thrombosis. We have utilized the prothrombin fragment F1+2 radioimmunoassay to quantitate factor Xa activity in the blood of 22 asymptomatic individuals with this clinical disorder not receiving antithrombotic therapy. The mean level of F1+2 was significantly elevated in these patients as compared to normal controls (3.91 vs. 1.97 nM, P less than 0.001). The metabolic behavior of 131 I-F1+2 was found to be similar in antithrombin-deficient subjects and normal individuals. The hemostatic system hyperactivity as measured by the F1+2 assay could be specifically corrected by raising the plasma antithrombin levels of the above asymptomatic individuals into the normal range. This study provides the first demonstration that the prethrombotic state can be biochemically defined as an imbalance between the production and inhibition of factor Xa enzymatic activity within the human circulation. It is known that antithrombin and alpha 1-proteinase inhibitor (PI) are the major inhibitors of factor Xa in human plasma in the absence of heparin. To further evaluate the mechanism by which antithrombin functions as an inhibitor of factor Xa in humans, we studied five patients who exhibited severe congenital deficiencies of alpha 1-PI. Our results indicated that the plasma of these subjects showed virtually identical decreases in plasma antifactor Xa activity in the absence of heparin when compared to antithrombin-deficient individuals, but the plasma F1+2 levels in the alpha 1-PI deficient population were not significantly different than normal. This data suggests that alpha 1-PI does not function as a major inhibitor of factor Xa in vivo, and that a tonically active heparin-dependent mechanism exists in humans for accelerating the neutralization of this enzyme by antithrombin.